Age- and sex-specific association of circulating osteocalcin with dynamic measures of glucose homeostasis. Issue 3 (March 2016) - Jung, K.; Kim, K.; Ku, E.; Kim, Y.; Lee, D.-H.; Choi, S.; Jang, H.; Shin, C.; Park, K.; Lim, S.
Abstract Summary Our study showed that serum osteocalcin levels are closely related to glucose metabolism in men of all ages and younger women. This association disappeared in postmenopausal women in which increases bone turnover rates. The association between serum osteocalcin levels and glucose homeostasis should be interpreted according to age and sex. Introduction Osteocalcin, a marker of bone formation, appears to be associated with glucose homeostasis. We investigated the age- and sex-specific association of serum osteocalcin level with variables related to glucose metabolism. Methods This study was based on cross-sectional analysis from 719 participants aged 20–85 years after excluding patients taking antidiabetic or antiosteoporotic drugs. The subjects were divided into four groups according to age and sex as follows: men <50 years (n  = 131), men ≥50 years (n  = 191), women <50 years (n  = 108), and women ≥50 years (n  = 279). Anthropometric and biochemical variables including insulin resistance (HOMA-IR) and β cell function (HOMA-β) from a 75-g oral glucose tolerance test, and serum 25-OH-vitamin D and parathyroid hormone levels were measured. Results The serum osteocalcin level was significantly higher in women aged ≥50 years compared with women <50 years (20.4 ± 7.8 vs. 17.9 ± 6.8 ng/ml, p  < 0.001), but there was no difference between men aged ≥50 years and men <50 years (16.4 ± 5.9 vs. 16.8 ± 6.0 ng/ml, p  = 0.905). The participants diagnosed with diabetes had lower serum osteocalcin levels than normal or prediabetic participants. Multivariable regression analyses including HOMA-IR and HOMA-β indicated that serum osteocalcin levels had a negative and independent association with HbA1c levels in men and women aged <50 years, but not in women ≥50 years. Conclusions Low osteocalcin levels are associated with impaired glucose metabolism in men and premenopausal women. The osteocalcin levels may be determined by factors related to bone metabolism in postmenopausal women. Our data suggest that the serum levels of osteocalcin associated with glucose homeostasis should be interpreted according to age and sex.